Crystal structure of 2-(adamantan-1-yl)-5-(4-bromophenyl)-1,3,4-oxadiazole - Alzoman, Nourah Z.; El-Emam, Ali A.; Ghabbour, Hazem A.; C. S., Chidan Kumar; Fun, Hoong Kun (International Union of Crystallography, 2014)
In the title molecule, C18H19BrN2O, the benzene ring is inclined to the oxadiazole ring by 10.44 (8). In the crystal, C—H interactions link the molecules in a head-to-tail fashion, forming chains extending along the c-axis direction. The chains are further connected by – stacking interactions, with centroid–centroid distances of 3.6385 (7) A ° , forming layers parallel to the bc plane.